The hunger of the gods ebook - Gwynne, John (The Bloodsworn Trilogy, 2022)
Packed with myth, magic, and bloody vengeance, John Gwynne's "masterfully crafted, brutally compelling, Norse-inspired epic" (Anthony Ryan) continues in The Hunger of the Gods . THE DEAD GODS ARE RISING. Lik-Rifa, the dragon god of legend, has been freed from her eternal prison. Now she plots a new age of blood and conquest.        As Orka continues the hunt for her missing son, the Bloodsworn sweep south in a desperate race to save one of their own–and Varg takes the first steps on the path of vengeance.        Elvar has sworn to fulfill her blood oath and rescue a prisoner from the clutches of Lik-Rifa and her dragonborn followers, but first she must persuade the Battle-Grim to follow her. Yet even the might of the Bloodsworn and Battle-Grim cannot stand alone against a dragon god.      Their only hope lies within the mad writings of a chained god. A book of forbidden magic with the power to raise the wolf god Ulfrir from the dead...and bring about a battle that will shake the foundations of the earth.   Praise for The Shadow of the Gods “There is not a dull chapter in this fantasy epic.” —Vulture (Best of the Year)   "A satisfying and riveting read. It’s everything I’ve come to expect from a John Gwynne book." —Robin Hobb   "A masterfully crafted, brutally compelling Norse-inspired epic." —Anthony Ryan   "A masterclass in storytelling . . . epic, gritty fantasy with an uncompromising amount of heart." —FanFiAddict   For more from John Gwynne, check out:   The Bloodsworn Trilogy The Shadow of the Gods The Hunger of the Gods   Of Blood and Bone A Time of Dread A Time of Blood A Time of Courage   The Faithful and the Fallen Malice Valor Ruin Wrath